Profil Penggunaan Obat Imunomodulator Masa Pandemi pada Konsumen dengan Imun yang Lemah di Apotek Kimia Farma Jatibarang Kota Indramayu - Vinda Anggraeni (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Based on data on the use of Immunomodulator drugs from 1,170 transactions, 64 transactions were obtained. Drugs given through prescriptions. Based on the data I obtained, the most prescriptions for immunomodulators occurred in April 2021 by doctors at Kimia Farma Pharmacy, Indramayu city with a total of 26 prescriptions. The purpose of the study is to determine the pattern of use (prescription or non-prescription) of consumers of immunomodulatory drugs at Kimia Farma Pharmacy, Indramayu City. This type of research uses a qualitative design with descriptive research methods. Data collection was carried out, namely all data that met the inclusion and exclusion criteria. The results showed that the sales of Immunomodulator drugs for the period April – June 2021 were 1,170. Based on the pattern of prescription use, there are 64 transactions, while the pattern for non-prescription use is 1,106 transactions. From the research I did, it can be concluded that the trade names of Immunomodulator drugs containing echinacea, meniran, and morindae in the Imunos Tablet and Fituno Tablet preparations are the most widely used, with the rule of taking 1 tablet a day and 2 tablets a day, and the dosage form is tablets.